E-aedes framework based on Geographical Information System: Stakeholder Perceptions - Muhammad Ilham; Nurul Islami; Faizar Abdurrahman; Suryadi Suryadi (Journal of Multidisciplinary Academic, 2020)
Effective and efficient information management can be achieved through the use of information technology. The emergence of the dengue virus is related to the uncontrolled breeding of the Aedes mosquito, also related to low levels of environmental hygiene. Control and prevention of the breeding of Aedes mosquitoes have been carried out in recent years, and still focused on eradication of the cases of Dengue Hemorrhagic Fever and Dengue Hemorrhagic Fever (DD & DDB). To prevent DD & DDB cases, the prevention action in decreasing number of DD & DDB is a major factor in controlling the spread of the disease and the breeding of Aedes mosquitoes. Accurate information is needed to provide a fast and accurate location notification of potential breeding areas for Aedes mosquitoes. This study aims to develop a framework for developing the Aedes (e-Aedes) mosquito warning system based on GIS (Geographic Information System), to identify a high-risk area for the Aedes mosquito breeding in residential area of Malaysia. Here, the expert interviews were conducted to confirm the initial framework of the study. This study chose qualitative and quantitative models as the research methodology. Thus, this study aimed to identify the awareness of community on DD &DDB issue. In order to achieve this study; we chose qualitative and quantitative models as the research methodology. This framework is verified through readiness, effectiveness and efficiency. The research results show a positive result, especially for effectiveness and efficiency which is can provide high reliability. This is shown from positive acceptance of respondents (the community) towards the framework of developing a GIS-based Aedes mosquito warning system (e-Aedes).